Quorum quenching strategy for biofouling control in membrane photobioreactor - Gunes, Goknur; Taskan, Ergin (Pergamon-Elsevier Science Ltd, 2022)
This study aims to reduce membrane fouling in membrane photobioreactor (MPBR) through the quorum quenching (QQ) strategy. For this purpose, the QQ beads (immobilized Rhodococcus sp. BH4) were added to the MPBR, and antifouling ability was evaluated in consideration of the changes in transmembrane pressure (TMP), extracellular polymeric substance (EPS), microbial community, and cake layer morphology on the membrane surface. The results showed that the TMP of control MPBR (MPBR-C) reached 818 mbar and 912 mbar on the operation hours of 35 and 170, while the TMP of experimental MPBR (MPBR-QQ) was only 448 mbar and 676 mbar, respectively. The QQ strategy effectively reduced the EPS content in MPBR. The microscopic observations indicated that the QQ diminished the cake layer formation and pore-blocking on the membrane surface. Com-parisons of 16S and 18S gene communities revealed minor differences between bacterial and eukaryotic species in MPBRs at phylum and class levels.
Keywords: Quorum quenching (QQ); Membrane photobioreactor (MPBR); Membrane biofouling; Microbial community